2016
DOI: 10.1075/sl.40.2.02fer
|View full text |Cite
|
Sign up to set email alerts
|

The prosody of Focus and Givenness in Hindi and Indian English

Abstract: This paper reports the results of two identical experiments, one in Hindi and one in Indian English, that elicited semi-spontaneous sentences containing a focused agent or a focused patient. The primary aim of the experiments was to investigate the prosodic correlates of information structure in the two languages and to explain these correlates with a phonological model. The resulting phonological model proposes that focus is realized with enhanced correlates of phrasing and not with prominence, at least not o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…As observed by [2], [9], and [11], our data also showed that each non-final constituent has an L tone on the stressed syllable followed by an H tone at the end of the constituent (Figure 1). The H tone either aligned with the case marker immediately following the focused noun (late as shown in the narrowly focused "zara=ko" in Figure 1) or with the last syllable of the focused noun (early as shown in the correctively focused "zara=ko" in Figure 1).…”
Section: F0 (Contour and Alignment)supporting
confidence: 88%
See 1 more Smart Citation
“…As observed by [2], [9], and [11], our data also showed that each non-final constituent has an L tone on the stressed syllable followed by an H tone at the end of the constituent (Figure 1). The H tone either aligned with the case marker immediately following the focused noun (late as shown in the narrowly focused "zara=ko" in Figure 1) or with the last syllable of the focused noun (early as shown in the correctively focused "zara=ko" in Figure 1).…”
Section: F0 (Contour and Alignment)supporting
confidence: 88%
“…Thus, correctively focused constituents were the longest, whereas selective and new information focus had the same relative constituent duration. While these results offer an interesting interplay of prosodic cues, a recent research by [11] has further added to the mass of contradictory findings.…”
Section: Focus and Prosody In Urdu/hindimentioning
confidence: 96%
“…A speaker with a rhythmic cadence was found to rely entirely on duration variation suggesting that specific prosody deficits may be identifiable through specific signal characteristics. Given that phrase boundary cues have been found to replace pitch accent cues in focused words in Indian English dialects [31], the acoustic correlates of phrase boundaries and the interaction of phrasing and prominence are also topics for future work. Finally, it is the prediction of goodness of reading rendition that is important.…”
Section: Discussionmentioning
confidence: 99%
“…Compensating for this ambiguity improved the average inter-rater agreement from kappa of 0.36 to a substantially better 0.64. This could also possibly indicate the frequent use of "prosodic words" by the speakers where a function word is prosodically attached to an adjacent content word [31].…”
Section: Dataset and Annotationmentioning
confidence: 99%
“…[11] refrained from assigning a tonal category and referred to the rise produced by Hindi English speakers as an LH contour. [26] proposed the same analysis for Hindi and IndE spoken by L1 Hindi speakers, and treated both the L and the H target as phrase tones that demarcate the edges of a minor prosodic unit. It is important to note that despite the presence of a "repetitive rising contour" in South Asian languages, tonal alignment of the rise is said to be a major source of cross-linguistic variation due to prominence patterns, segmental and lexical features across the languages spoken in the subcontinent [2].…”
Section: Introductionmentioning
confidence: 99%